1979
DOI: 10.1111/j.1471-4159.1979.tb00353.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF ACUTE HYPERTHERMIA ON POLYRIBOSOMES, IN VIVO PROTEIN SYNTHESIS AND ORNITHINE DECARBOXYLASE ACTIVITY IN THE NEONATAL RAT BRAIN

Abstract: Abstract— —Acute hyperthermia produces in situ disaggregation of brain polyribosomes in infant rats, as determined by electron microscopy. Protein synthesis is inhibited in infant, but not weanling, rat brain by 45 min of hyperthermia; this inhibition is reversed during a 2 h recovery period at normothermic conditions. Hepatic protein synthesis was inhibited less than that of brain. Acute hyperthermia also leads to a profound loss of ornithine decarboxylase activity in brain; during recovery the activity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Two procedures that were intended to be controls for the intracerebral injection of actinomycin D, drilling burr holes without puncturing the dura, and an intracerebral injection of mannitol (vehicle for actinomycin D), also induced ODC activity (Table I), probably due to mechanical and thermal trauma associated with drilling into the skull and injection damage. Stimulation of brain ODC activity by intracerebral injections and hyperthermia is consistent with previous reports (Millan et al. 1979: Hietala, 1983).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Two procedures that were intended to be controls for the intracerebral injection of actinomycin D, drilling burr holes without puncturing the dura, and an intracerebral injection of mannitol (vehicle for actinomycin D), also induced ODC activity (Table I), probably due to mechanical and thermal trauma associated with drilling into the skull and injection damage. Stimulation of brain ODC activity by intracerebral injections and hyperthermia is consistent with previous reports (Millan et al. 1979: Hietala, 1983).…”
Section: Resultssupporting
confidence: 92%
“…For example, noxious conditions that interrupt energy metabolism or other critical processes can impair protein synthesis and cause the rapid influx of calcium into the injured cell. Brain protein synthesis is inhibited by metabolic, chemical, and thermal injuries (Kleihues et al, 1975;Moskowitz et a]., 1977;Millan et al, 1979), and abnormal proteins are produced after injection of the amino acid analog L-canavanine (Waterlow et al, 1978). Recovery from disruption of the homeostatic balance between protein synthesis and degradation may require preferential production of ( I ) proteins with short half-lives, such as ODC, to compensate for their rapid loss (e.g., after ischemia; Kleihues et al, 1975), or (2) other proteins required for the recovery process.…”
Section: Odc and Brain Injurymentioning
confidence: 99%
“…Because the brain is more easily damaged by high temperatures than other bodily organs (Heikkila & Brown, 1979;Millan, Murdock, Bleier, & Siegel, 1979), a number of species have evolved physiological mechanisms that selectively cool the brain during exercise and during exposure to high air temperatures. For example, Crawford (1972) studied a lizard species (Sauromalus obesus) that, when panting, can maintain brain temperature nearly 3ЊC below an air temperature of 45ЊC.…”
Section: Selective Brain Cooling In Reptiles Birds and Mammalsmentioning
confidence: 99%
“…Since the 75K and 95K proteins are induced under similar conditions in a number of different cultured cell lines, it has been suggested that these proteins may be important for cell survival under stressful conditions such as temperature elevation and energy deprivation (Kelley and Schlesinger, 1978). Brain functions are particularly sensitive to such stresses (Ritter and Ritter, 1977;Millan et al, 1979). In addition to providing information on the effect of the psychotropic drug LSD on protein synthesis in the mammalian brain, our present studies demonstrate the sensitivity of the translational apparatus in the brain to hyperthermia.…”
Section: Discussionmentioning
confidence: 99%